Political Change in the Middle East: An Attempt to Analyze the "Arab Spring" - Martin Beck; Simone Hüser (German Institute of Global and Area Studies (GIGA), 2012)
This article deals with the Arab Spring as a process of deep political change in the Arab world, previously the only major world area where authoritarianism persisted unchallenged for decades. While in various countries of the Arab world mass protests in 2011 forced rulers to resign, other authoritarian regimes have - despite political and economic pressure - so far been able to remain in power, or have even been only insignificantly affected. This paper applies central social science approaches in order to analyze recent developments in the region - a major task of theoretically oriented social sciences in the coming years. In addition to providing an overview of the existing literature on the Arab Spring, the article examines the empirical results of political diversification in the Arab world. A two-by-two matrix of political rule that differentiates according to the type of rule and the degree of stability is presented and discussed. Although the analysis draws heavily on rent theory, it also applies findings from transition theory and revolution theory to illuminate the current political dynamics in the Middle East.
Keywords: 300; Arab Spring; Middle East; rent theory; revolution theory; transition theory; democratization; authoritarianism; political and economic liberalization; Politischer Wandel; Politische Unruhen; Systemtransformation; Rententheorie; Mittlerer Osten